Analysis of Multiple Input Multiple Output-Orthogonal Frequency Division Multiplexing with Dynamic Optimal Power Allocation - Srinivasulu, Owk; Kumar, P. Rajesh (Engineering, Technology & Applied Science Research, 2024)
Multiple Input Multiple Output (MIMO) is a technology that combines multiple antennas and Orthogonal Frequency Division Multiplexing (OFDM) modulation to increase the data rate and spectral efficiency of wireless communication systems. Equalization problems are one of the key issues with MIMO-OFDM systems, which are caused by multiple antennas and subcarriers. Optimal Power Allocation (OPA) in MIMO-OFDM is a critical component for achieving high spectral efficiency and improving the overall performance of the system. OPA refers to the process of allocating power to the different subcarriers and antennas in MIMO-OFDM systems in an optimal way. This study proposes the Dynamic OPA (DOPA) algorithm for MIMO-OFDM systems to dynamically adjust power allocation based on the changing channel conditions and reduce pilot contamination issues. This approach allocates more power to subcarriers and antennas with better channel conditions and less power to subcarriers and antennas with worse channel conditions. DOPA in MIMO-OFDM systems is necessary to maximize data rates, minimize interference, improve system capacity, and reduce power consumption. Simulation results showed that the proposed MIMO-OFDM-DOPA had reduced bit error rates, mean square error, and transmitter power and increased energy efficiency and capacity compared to existing state-of-the-art methods.